Hurry up, Houdini! - Osborne, Mary Pope.; Murdocca, Sal (New York : Random House, 2013)
Join Jack and Annie as they as they meet one of the world's most famous illusionists, Harry Houdini.
3.7
3-6
520L
M
Also numbered as Magic tree house Merlin missions bk. 22
Keywords: Houdini, Harry, -- 1874-1926 -- Fiction; Time travel -- Fiction; Magicians -- Fiction; Magic -- Fiction; Tree houses -- Fiction; Time travel -- Fiction; Magicians -- Fiction; New York (N.Y.) -- History -- 20th century -- Fiction